Bentuk Lahan Geomorfologi Di Daerah Gunungapi Ambang, Bolaang Mongondow Timur - Sumarjis, Suly Ayu; Arifin, Yayu Indriati; Hutagalung, Ronal; Akase, Noviar; Manyoe, Intan Noviantari (Journal of Applied Geoscience and Engineering, 2023)
Sulawesi or Celebes is located in the central part of the Indonesian archipelago which has interesting geological potential to be developed. One of this interesting area is known as Ambang volcano area. Ambang volcano is one of the active volcanoes in North Sulawesi. Administratively, the research area is located in Bongkudai Baru Village, Modayag sub-district, East Bolaang Mongondow district, mapped at coordinates N 0°45'58.89'' and E 124°24'13.04''. This study is aimed to analyze volcanic geomorphological units using satellite imagery and surface geological mapping. The results showed that the geological conditions of the study area consist of 4 lithologies i.e volcanic breccia, andesite, agglomerate and sandstone rocks. Based on the morphographic and morphogenetic analysis of the study area which refers to the Van Zuidam and Verstapen 1985 classification, the study area is divided into five landforms i.e fumarole and solfatara ambang volcanic, ambang volcanic cone, plains and fluvial slope feet of ambang volcano, denudational hill ambang volcanoes and lake units.